First-principles study of superconducting in LiFeAs: FM, AFM, and NM states via DFT and DFT+U techniques - Manza Zityab Kasiab; Kumneger Tadele; Mesfin Asfaw Afrassa; Omololu Akin-Ojo (AIP Advances)
The interplay between magnetism and superconductivity in Fe-based superconductors remains a topic of significant interest. This study investigates the electronic structure and superconducting properties of LiFeAs in ferromagnetic (FM), antiferromagnetic (AFM), and non-magnetic states using Density Functional Theory (DFT) and DFT+U approximations. Notably, the DFT approximation favors AFM coupling, but DFT+U stabilizes an FM configuration in spin-polarized simulations. The DFT approximation predicts a lattice parameter of 3.651 Å, a mean-field AFM/FM transition temperature [Tc(MFA)] of 38.7 K, and a magnetic moment of 1.47 μB per Fe atom. In contrast, DFT+U yields a lattice parameter of 3.768 Å, closely matching the experimental value of 3.771 Å. It also predicts a significantly enhanced Tc(MFA) of 464.2 K and a magnetic moment of 3.13 μB per Fe atom. The significance of these findings lies in the ability of DFT+U to capture electron correlation effects better, leading to structural and magnetic properties that align more closely with an experimental observation of 3.42 μB. Finally, the DFT+U approximation structure increases bond length and angle by 0.1995 Å and 1.424°, respectively, compared to the DFT approximation. The non-magnetic state appears most favorable for superconductivity, whereas FM and AFM states suppress superconducting behavior because of spin polarization effects. This analysis provides valuable insights into the delicate balance between magnetism and superconductivity in Fe-based materials, contributing to the theoretical understanding of their electronic properties.